An annotated bird checklist for Gam island, Raja Ampat, including field notes on species monitoring and conservation - Schrader, Julian; Mühlenberg, Michael; Stinn, Christina; Mühlberger, Fabian; Weinrich, Christoph; Hofmann, Tim; Kalor, John D; Moeljono, Soetjipto; Parsch, Christoph; Sattler, Cornelia (Forest and Society, 2020)
Species checklists are a fundamental component of biodiversity research. They foster understanding of species distributions and habitat preferences, thus reducing gaps of knowledge in geographical occurrences of species. Especially in light of the limited availability of data on species distributions for Tanah Papua, an increasing scientific focus on the region is crucial to foster and refine the knowledge of species occurrences and to inform potential conservation planning. Despite a strong focus on conservation of Raja Ampat´s marine areas, surprisingly few studies have focused on the terrestrial biodiversity of the archipelago. As a consequence, detailed species checklists are largely missing. Here, we provide a preliminary bird species checklist for the island of Gam and its surrounding islands, located in the central Raja Ampat archipelago. During nine sampling periods between 2013 and 2019, we recorded 132 bird species in six distinct habitat types. Of the detected species, six are considered threatened by IUCN Red List criteria. We further recorded three new species for Gam Island, thereby expanding their known extent of occurrence.